Antibacterial Activity of Essential Oils from the Leaves of Adiantum capillus Ã¢â‚¬â€ veneris Linn. - B, Victor; M, Maridass; U, Ramesh; J.M.A, Prabhu (Malaysian Journal of Science, 2003)
This paper reports on the antibacterial activity of the essential oils from the leaves of $Adiantum$ $capillus-veneris$ Linn. A lemon yellow colored essential oil of 0.55% v/w was extracted from the leaves by hydrodistillation. The essential oil exhibited maximum inhibitory activity against $Salmonella$ $typhi$. Mild antibacterial activity was detected for $Pseudomonas$ species., $Klebsiella$ $pneumoniae$ and $Streptococcus$ $pyogenes$.